2009
DOI: 10.1088/1748-6041/4/4/045008
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties of mesoporous copper-doped silica xerogels

Abstract: Mesoporous copper-doped silica xerogels (m-SXCu) with antibacterial properties were synthesized by a sol-gel process, and the morphology, structure and composition of m-SXCu were characterized. The results show that m-SXCu5 with a high surface area of 463.1 m(2) g(-1) have a mesoporous structure with a pore size of about 2 nm. The addition of Cu from 1 to 5 wt% to m-SXCu had a slight effect on the surface area and a not-so-obvious effect on the mesoporous size of m-SXCu. Cu ions can be released from m-SXCu int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…20 Biocomposites containing BG and polymers have attracted increasing attention as promising biomaterials for bone tissue regeneration. 21,22 In this study, Li-MBG was incorporated into copolymer of mPEG-PLGA-b-PLL to form biocomposite scaffolds by solvent casting and particulate leaching method.…”
Section: Discussionmentioning
confidence: 99%
“…20 Biocomposites containing BG and polymers have attracted increasing attention as promising biomaterials for bone tissue regeneration. 21,22 In this study, Li-MBG was incorporated into copolymer of mPEG-PLGA-b-PLL to form biocomposite scaffolds by solvent casting and particulate leaching method.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] The non-ionic block copolymer EO 20 PO 70 EO 20 (Pluronic P123, molecular weight =5,800, Sigma-Aldrich, St Louis, MO, USA) was used as the template agent. In brief, 4.8 g of P123 was dissolved in 480 mL of 0.1 M HCl aqueous solution at 50°C to obtain a white emulsion.…”
Section: Preparation and Characterization Of N-mzs Xerogelsmentioning
confidence: 99%
“…[1][2][3][4][5][6] To date, some studies have reported the design of drug-delivery systems based on the nanoporous materials for loading therapeutic molecules, such as chemical drugs, peptides, and proteins. 7,8 As an effective vector-delivering therapeutic molecules, the nanoporous materials with the pore size of a few nanometers have high capacity to encapsulate large amounts of drugs/biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 PLLA, an aliphatic polyester and also a biodegradable polymer, has been widely studied due to its biocompatibility, biodegradability, and low immunogenicity to explore advanced tissue-engineering applications. [17][18][19][20][21][22][23] Despite the aforementioned advantages of PLLA, it also possesses some signicant drawbacks, such as low hydrophilicity, poor cell affinity, difficulty in controlling the degradation, and the generation of local acidic conditions during degradation. 24,25 To improve the functions of PLLA for biomedical applications, modications with other molecules including polyethylene glycol (PEG), polypyrrole, and poly(L-lysine) (PLL) covalently or noncovalently, have been investigated.…”
Section: Introductionmentioning
confidence: 99%